2019
DOI: 10.1371/journal.pone.0217143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of environmental risk factors for chronic obstructive pulmonary disease exacerbation: A case-crossover study (2004-2013)

Abstract: Purpose We aim to assess if air pollution levels and climatological factors are associated with hospital admissions for exacerbation of chronic obstructive pulmonary disease (COPD) in Spain from 2004 to 2013. Methods We conducted a retrospective study. Information on pollution level and climatological factors were obtained from the Spanish Meteorological Agency and hospitalizations from the Spanish hospital discharge database. A case-crossover design was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
3
22
0
2
Order By: Relevance
“…5 Another potential trigger for such exacerbations is short-term exposures to extreme temperature. 6 Extremes of temperature, both cold and hot, have also been associated with excess mortality and morbidity among patients suffering from COPD. 7 Previously reported works have demonstrated conflicting results on the correlation of ambient temperature and COPD hospitalization, emergency room visits, and outpatient clinic visits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Another potential trigger for such exacerbations is short-term exposures to extreme temperature. 6 Extremes of temperature, both cold and hot, have also been associated with excess mortality and morbidity among patients suffering from COPD. 7 Previously reported works have demonstrated conflicting results on the correlation of ambient temperature and COPD hospitalization, emergency room visits, and outpatient clinic visits.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previously reported works have demonstrated conflicting results on the correlation of ambient temperature and COPD hospitalization, emergency room visits, and outpatient clinic visits. 6,[8][9][10][11][12][13] Several published studies suggest that a decline in ambient temperature is linked with a higher susceptibility to COPD risk. 6,[8][9][10] Other researches have reported higher COPD risks during high temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outdoor air pollution in studies elsewhere consistently showed greater likelihood of respiratory symptoms in both children and adults [24][25][26][27] and COPD. [8][9][10] We hypothesize, that the basic air pollution level in Almaty is so high, that a distance of 50 to 100 meters from a major road cannot play a role in worsening the symptoms. Despite known very high levels of air pollution in Almaty, including particulate matter, especially in winter, no scientific analysis of air pollution levels has been published to date.…”
Section: Figurementioning
confidence: 99%
“…Finally, ambient air pollution is often not regarded as an important confounder in the occupational studies, despite growing evidence that it is independently associated with greater risk of COPD. [8][9][10] Therefore, the aim of the current analysis was to ascertain the effect of lifelong occupational history, ambient air pollution, and biochemically verified smoking status with COPD in general population of one the largest cities in Central Asia, Almaty.…”
Section: Introductionmentioning
confidence: 99%